Seasonal genetic variation and genetic structure of Spodoptera exigua in Liaoning Province, Northeast China: insights from 11 years of microsatellite data - Yu, Ming-Li; Xiu, Xian-Zhi; Wang, Jin-Yang; Cao, Xin-Yi; Qin, Fa-Liang; Wang, Xing-Ya; Zhou, Li-Hong (PeerJ, 2025)
Background The beet armyworm (BAW), Spodoptera exigua, is a destructive migratory pest worldwide that has caused severe economic losses in China’s major crop-producing regions. To control this pest effectively, it is crucial to investigate its seasonal genetic variation and population genetic structure in northern China. Methods In this study, we used eight nuclear microsatellite loci to investigate the seasonal genetic variation and genetic structure of BAW in Shenyang, Liaoning Province, Northeast China, from 2012–2022, collected from a single location on Welsh onion. Results Microsatellite data revealed moderate levels of genetic variation among 50 seasonal populations of BAW sampled from 2012–2022, along with significant genetic differentiation among these populations. Neighbor-joining dendrograms, STRUCTURE analysis, and principal coordinate analysis (PCoA) revealed two genetically distinct groups: the SY2012–2018 group and the SY2019–2022 group. Our results revealed seasonal variation in the genetic subconstruction at this location, which may be related to the presence of different migratory individuals throughout the year. Accordingly, our unique insights into the population genetics of BAW will contribute to the development of effective management strategies for this migratory pest.
Keywords: Spodoptera exigua; Genetic structure; Microsatellites; Migration; Seasonal variation; Welsh onion